2017
DOI: 10.1074/jbc.m117.780239
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization of DNA sequences directs the assembly of bacterial chromatin by a nucleoid-associated protein

Abstract: Structural differentiation of bacterial chromatin depends on cooperative binding of abundant nucleoid-associated proteins at numerous genomic DNA sites and stabilization of distinct long-range nucleoprotein structures. Histone-like nucleoid-structuring protein (H-NS) is an abundant DNA-bridging, nucleoid-associated protein that binds to an AT-rich conserved DNA sequence motif and regulates both the shape and the genetic expression of the bacterial chromosome. Although there is ample evidence that the mode of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 56 publications
7
29
0
Order By: Relevance
“…In agreement with previous reports , we found that both the absence of H‐NS or the presence of extra H‐NS led to a dramatic increase in the number of cells with uncompacted nucleoids in a medium‐independent manner (Figure ). An increase in the number of cells with uncompacted nucleoids was also observed in the hns 206 mutant (Figure ), indicating that the availability of H‐NS and fully functional H‐NS is required for correct nucleoid compaction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports , we found that both the absence of H‐NS or the presence of extra H‐NS led to a dramatic increase in the number of cells with uncompacted nucleoids in a medium‐independent manner (Figure ). An increase in the number of cells with uncompacted nucleoids was also observed in the hns 206 mutant (Figure ), indicating that the availability of H‐NS and fully functional H‐NS is required for correct nucleoid compaction.…”
Section: Discussionsupporting
confidence: 93%
“…At least 12 distinct types of NAPs have been described in E. coli while IHF, HU, Fis, and H‐NS are well characterized . The 15.5 kDa H‐NS protein is believed to play an important role in nucleoid compaction and organization by bridging distant DNA segments . Also IHF, as a member of nucleoid‐associated proteins, promotes nucleoid compaction .…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic shock, besides redirecting RNAP binding in the genome [85], could also affect the binding of NAPs, which depends on both sequence composition and DNA topology [86][87][88][89][90]. For example, the binding of the global repressor H-NS [91] is modulated by ionic composition, sequence organization, and DNA topology [88,[92][93][94][95][96][97]. H-NS preferentially binds A/T-rich sequences and represses transcription by bridging DNA duplexes and forming inter-wound filaments [98,99].…”
Section: Testing the Dynamical Behavior Of Codos By Reporter Constructsmentioning
confidence: 99%
“…As a first step toward in vitro reconstitution of bacterial chromatin, we compared H-NS filaments formed on purified, deproteinized genomic DNA (gDNA) to in vivo H-NS binding patterns determined by ChIP-seq. We predicted that H-NS filaments would nucleate at AT-rich, high-affinity sites Japaridze et al, 2017;Lang et al, 2007) but that strong contributions of other DBPs to H-NS filament locations would make the in vitro and in vivo patterns different. To define locations of H-NS filament formation on sheared gDNA, we captured the reconstituted filaments by binding to nitrocellulose filters, and then determined 6/11/2020 filament locations by HT-sequencing of DNA recovered from the filters.…”
Section: H-ns Nucleoprotein Filaments Can Be Reconstituted Using Genomentioning
confidence: 99%